Parents and Peers in Child and Adolescent Development: Preface to the Special Issue on Additive, Multiplicative, and Transactional Mechanisms - Amanda W. Harrist; Michael M. Criss (MDPI AG, 2021)
Parents and peers play critical roles in the socialization of children and adolescents, yet investigations on the role played by parents vs. peers have been largely separate for many years. To address this problem, we invited leading scholars in the field to collectively tell a complex story of the part that parents and peers together play in the development of children and adolescents. The resulting Special Issue is a collection of papers highlighting current conceptualizations and empirical work in this area, with a focus on additive, multiplicative, and transactional mechanisms that link parent and peer relational contexts to each other and to child/adolescent social and emotional development. Two papers present new conceptual models, six illustrate empirical work in the field, and one paper that provides a comprehensive review of the literature. The stories that are conveyed in the issue are both innovative and complex.